Deuterium Permeation Behavior in Fe Ion Damaged Tungsten Studied by Gas-Driven Permeation Method. (2nd April 2020) - Zhao, Mingzhong; Nakata, Moeko; Sun, Fei; Hatano, Yuji; Someya, Yoji; Tobita, Kenji; Oya, Yasuhisa
Abstract: The deuterium (D) permeation behavior for 1 displacement per atom Fe 2+ damaged tungsten (W) was studied by the gas-driven permeation method and compared with undamaged W. The results of thermal desorption spectroscopy showed that dislocation loops and voids were formed in damaged W. It was found that the D permeation behavior in W was affected by irradiation defects. The effective diffusivity and permeability in the damaged W were lower than that in undamaged W. However, the difference in effective diffusivity and permeability between the undamaged sample and the damaged sample was reduced with increasing the heating temperature. Under 965 K, which was enough for D detrapping from voids, the permeability for damaged W was consistent with that for undamaged W.